The great escape [videorecording (DVD)] - Sturges, John, 1910-1992; McQueen, Steve, 1930-1980; Garner, James. 1928-2014; Attenborough, Richard; Donald, James, 1917-1993; Bronson, Charles, 1921-2003; Pleasence, Donald; Clavell, James; Burnett, W. R. (William Riley), 1899-1982; Brickhill, Paul (MGM Home Entertainment, 2004)
A World War II melodrama about the escape of British and American flyers from a maximum-security German prison camp.